Alternative polyadenylation and dynamic 3′ UTR length is associated with polysome recruitment throughout the cardiomyogenic differentiation of hESCs - Hansel-Frose, Aruana F. F.; Allmer, Jens; Friedrichs, Marcel; dos Santos, Hellen Geremias; Dallagiovanna, Bruno; Spangenberg, Lucía (Frontiers in Molecular Biosciences, 2024)
Alternative polyadenylation (APA) increases transcript diversity through the generation of isoforms with varying 3’ untranslated region (3’ UTR) lengths. As the 3’UTR harbors regulatory elements target sites, such as miRNAs or RNA binding proteins, changes on this region can impact post-transcriptional regulation and translation. Moreover, the APA landscape can change based on cell type, cell state or condition. Given that APA events can impact protein expression, investigating translational control is crucial for comprehending the overall cellular regulation process. Revisiting data from polysome profiling followed by RNA sequencing, we investigated the cardiomyogenic differentiation of pluripotent stem cells by identifying the transcripts that show dynamic 3’UTR lengthening or shortening which are being actively recruited to ribosome complexes. Our findings indicate that dynamic 3’UTR lengthening is not exclusively associated with differential expression during cardiomyogenesis, rather than with recruitment to polysomes. We confirm that the differentiated state of cardiomyocytes show preference for shorter 3’UTR in comparison to the pluripotent stage, although preferences vary during the days of differentiation process. The most distinct regulatory changes are seen in day 4 of differentiation, which is the mesoderm commitment time point of cardiomyogenesis. After identifying the miRNAs that would target specifically the alternative 3’UTR region of the isoforms, we constructed a gene regulatory network for the cardiomyogenesis process, in which genes related to cell cycle were identified. Altogether our work sheds light on the regulation and dynamic 3’UTR changes of polysome-recruited transcripts that take place during cardiomyogenic differentiation of pluripotent stem cells.